Pengelolaan Merdeka Belajar dan Kampus Merdeka - Nelfia Nofitri; Ilmi, Darul (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2023)
The rapid development of science and technology has brought many changes in various aspects of life. This of course requires people to be able to adapt to the times. To answer the challenges of that era, it was necessary to have the presence of the Independent Learning Independent Campus (MBKM) to create a new paradigm in the world of education, including higher education. The Minister of Education and Culture's 2020 policy with the MBKM concept is considered relevant and appropriate to implement in the current democratic era. According to Nadiem Makarim, the basic concept of choosing independent learning is because it was inspired by the philosophy of K.H. Dewantara with an emphasis on independence and independence. MBKM consists of two essential concepts, namely "Free Learning" and "Independent Campus". First, the concept of independent learning means freedom of thought. According to Nadiem Makarim, the essence of freedom of thought must be initiated by educators. This view must be seen as an effort to respect changes in learning in educational institutions, both in primary, secondary and tertiary schools. Second, the independent campus is a continuation of the concept of independent learning. The independent campus is an attempt to release the shackles to be able to move more easily